Evolution of iGluR ligand specificity, polyamine regulation, and ion selectivity inferred from a placozoan epsilon receptor - Anhadvir Singh; Boris S. Zhorov; Luis A. Yanez-Guerra; Alessandra Aleotti; Chloe C. Koens; C. Defne Yanartas; Yunqi Song; Federico Javier Miguez Cabello; Derek Bowie; Adriano Senatore (Communications Biology)
Abstract Epsilon ionotropic glutamate receptors (iGluRs) are a recently defined clade of neurotransmitter receptors that are found in all major metazoan lineages that are distinct from α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), kainate, delta, phi (i.e., AKDF) and N-methyl-D-aspartate NMDA receptors. Here, we explore the evolution of iGluRs by generating a broad species-guided phylogeny of eukaryotic iGluRs and a comprehensive phylogeny of placozoan receptors, uncovering marked diversification of epsilon type receptors within Placozoa. Functional characterization of one epsilon receptor from the placozoan species Trichoplax adhaerens, named GluE1αA, reveals sensitivity to glycine, alanine, serine, and valine, but not glutamate. We demonstrate that changing just three amino acids in the ligand binding domain could convert ligand specificity of GluE1αA from glycine to glutamate, also causing nascent sensitivity to AMPA and increased sensitivity to the blocker 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX). We also demonstrate that an atypical serine in the pore Q/R/N site confers diminished Ca2+ permeation and sensitivity to polyamine block, imposing similar effects on the human GluA2 receptor, and that a conserved aspartate four amino acids downstream of the Q/R/N site is crucial for polyamine regulation. Thus, key molecular determinants for polyamine regulation are conserved between AKDF and epsilon receptors.